Przykłady Kształtowania Belek Sprężonych - Brandt, A. (Engineering Transactions, 1964)
The subject matter of this paper, which is a continuation of the author's former works is the research of the optimum form of a prestressed concrete beam. Sec. 2 brings a solution of the design problem of a rectangular beam by equalizing normal stresses at the ends. The considerations of Sec. 3 concern a rectangular beam designed for minimum potential of elastic forces produced by the useful load. Sec. 4 discusses the design of a double-tee beam with the same condition. In. Sec. 5 devoted also to the design of a double-tee beam is considered a factor originating form the shear forces and hitherto disregarded. In the last section is described an approximate method for determining the influence of shear forces on the form of a double-tee beam. Each particular solution is illustrated by numerical examples and diagrams of the functions obtained expressing the form of the beams.